Question Solved1 Answer Find ƒ' (c) if it exists. ƒ (x) = 5x²³³ and c = −8 (Express numbers in exact form. Use symbolic notation and fractions where needed. Enter DNE if the derivative does not exist.) f' (c) = The function f does not have a derivative at c, because the one-sided limits are not equal. has a derivative at c. does not have a derivative at c, because there is a cusp Find ƒ' (c) if it exists. ƒ (x) = 5x²³³ and c = −8 (Express numbers in exact form. Use symbolic notation and fractions where needed. Enter DNE if the derivative does not exist.) f' (c) = The function f does not have a derivative at c, because the one-sided limits are not equal. has a derivative at c. does not have a derivative at c, because there is a cusp at c. does not have a derivative at c, because the tangent to the graph at e is vertical.

YDZDKY The Asker · Calculus

Transcribed Image Text: Find ƒ' (c) if it exists. ƒ (x) = 5x²³³ and c = −8 (Express numbers in exact form. Use symbolic notation and fractions where needed. Enter DNE if the derivative does not exist.) f' (c) = The function f does not have a derivative at c, because the one-sided limits are not equal. has a derivative at c. does not have a derivative at c, because there is a cusp at c. does not have a derivative at c, because the tangent to the graph at e is vertical.
More
Transcribed Image Text: Find ƒ' (c) if it exists. ƒ (x) = 5x²³³ and c = −8 (Express numbers in exact form. Use symbolic notation and fractions where needed. Enter DNE if the derivative does not exist.) f' (c) = The function f does not have a derivative at c, because the one-sided limits are not equal. has a derivative at c. does not have a derivative at c, because there is a cusp at c. does not have a derivative at c, because the tangent to the graph at e is vertical.
See Answer
Add Answer +20 Points
Community Answer
NG12SG The First Answerer
See all the answers with 1 Unlock
Get 4 Free Unlocks by registration

Solytion: Given.{:[f(x)=5x^(2//3)" and "c=-8],[=>f^(')(x)=5*(2)/(3)*x^(2//3-1)],[=>f^(')(x)=(10)/(3)*x^(-1//3)quad:'(d)/(dx)(x^(h))=hx^(h-1)]:}Now{:[f^(')(c)=(10)/(3)(c)^(-1//3)],[=(10)/(3)(-8","-1//3",":.c= ... See the full answer